PEMBERDAYAAN KELOMPOK TERNAK KAMBING JAWA RANDU DI DESA DAYUNG KUSUMA MRANGGEN KABUPATEN DEMAK MELALUI PELATIHAN PEMBUATAN PAKAN SILASE - Muh Samsudin,; Arif Nugroho Rahman, (KRIDA CENDEKIA, 2025)
Feed plays an important role in supporting livestock businesses, especially Javanese randu goats. The availability of feed, especially fresh greens, is quite abundant in Dayung Kusuma, Mpranggen, Demak Regency. However, there are obstacles in dividing time for work and finding fresh greens. This community service activity aims to provide a solution by educating and assisting in making silage feed. Making silage feed is one alternative that can be used to overcome existing problems, so that there is no need to look for green feed every day. The purpose of this community service is to educate and assist in the process of making silage feed. This community service activity is carried out using lecture methods, discussions and practices for making silage feed using field grass and elephant grass. The responses of participants generally showed enthusiasm, eagerness in practicing making silage feed. After the community service activity, it is hoped that participants will be more enthusiastic in raising Javanese randu goats because the obstacle of finding fresh green feed every day has been replaced with silage feed